Arabic poetry : trajectories of modernity and tradition - Mūsawī, Muḥsin Jāsim (Routledge studies in Middle Eastern literatures., 2006)
Since the late 1940s, Arabic poetry has spoken for an Arab conscience, as much as it has debated positions and ideologies, nationally and worldwide. This book tackles issues of modernity and tradition in Arabic poetry as manifested in poetic texts and criticism by poets as participants in transformation and change. It studies the poetic in its complexity, relating to issues of selfhood, individuality, community, religion, ideology, nation, class and gender.Al-Musawi also explores in context issues that have been cursorily noticed or neglected, like Shi'i poetics, Sufism, women's poet.